Wykorzystanie narzędzi ETL do oceny materiału dydaktycznego w nauczaniu zdalnym - Smok, Barbara (The ETL tools in didactic materials assessment process within distance learning, 2005)
Rapid technology development and its implementation leads towards the information socjety where education plays important role. Open education as well as distance learning are getting more and more popular. Application of modem technologies in education system is basis for these fast changes in education. E-leaming platform enables to carry on tests assessing particular parts of didactic materials. The paper presents the usage of the ETL tools in didactic materials assessment process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 247-257